PROFESIONALISME APARATUR SATUAN POLISI PAMONG PRAJA KABUPATEN SUMBAWA BARAT - Aufa Rahman; Darmanto Darmanto; Diki Diki (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Professionalism is a most to be owned by the State Civil Apparatus in today's dynamic era. This research tries to explore two important things in looking at Professionalism in Pamong Praja Police Unit of West Sumbawa Regency, that is: How is the professionalism of Pamong Praja Police Unit of West Sumbawa Regency and what the factors that influence it are. The author tries to explain these two things by combining between the theory and concepts put forward by experts with the field conditions that occur. So that we can find out whether Pamong Praja Police Unit of West Sumbawa Regency is Professional, Towards Professional or Not Professional at all. The research method used is descriptive qualitative research because it is related to the selected problem that is telling social phenomena that does not intend to make calculations qualitatively or using statistics but rather lead to exploitation of public expression and events that occur. The Source Data in this study are: Informants, Events, and Documents. Data collection techniques used in this study are: Interview, Observation, and Documentation. Pamong Praja Police Unit has a duty to maintain and organize public order and tranquility, to carry out Community Protection, to enforce the Regional Regulation and the Decision of the Regional Head. To carry out these tasks required high professionalism, to know that there are several indicators used in viewing the professionalism of Pamong Praja Police Unit of West Sumbawa Regency are: a) The intellectual capacity of employees; b) Standard of work; c) Moral and ethical standards.